Shear bond and shear fatigue of geosynthetic interlayered asphalt overlays - Silva, Matheus Pena da Silva e (Universidade Federal de São Carlos, 2024)
Innovative applications of paving geosynthetics have emerged to reduce reflective crack propagation and moisture infiltration in pavement structures, leading to the development of various products such as paving grids, composites, and mats. The diversity within the geosynthetic market encompasses products with differing properties. Ensuring an adequate bond between paving geosynthetics and adjacent asphalt layers is crucial for proper asphalt system performance. However, the impact of paving geosynthetic properties, along with tack coat types and rates, on bond properties remains uncertain. This study aims to assess the influence of multiple factors on interface shear bond and shear fatigue parameters. A comprehensive testing program utilizing a multifunctional interface shear tester and laboratory-prepared double-layered asphalt specimens with paving geosynthetics was conducted. The experimental setup involved nine types of paving geosynthetics, two tack coat types, and varying tack coat rates. Results from interface shear bond tests demonstrate significant effects from the paving geosynthetic type, tack coat type and rate, as well as their interactions. Multiple linear regression analysis identified geogrid mesh area, paving geosynthetic thickness, fabric backing thickness, and presence of bitumen coating as key factors influencing interface shear strength. A predictive model for geosynthetic-reinforced asphalt layers' interface shear strength based on geosynthetic properties is proposed. Additionally, shear fatigue test results revealed that bitumen content of the geosynthetic coating, type of fabric in the geosynthetics, and geogrid mesh area predominantly affect shear fatigue life. Furthermore, a correlation between shear fatigue life and interface bond parameters was observed. Overall, these findings enhance understanding of geosynthetic properties affecting short and long-term bonding properties, as well as the impact of tack coat type and rate, and, in the case of shear fatigue tests, test frequency.
Aderência de interface e fadiga por cisalhamento entre camadas asfálticas e geossintético
Keywords: Geossintéticos na pavimentação; Dupla camada de asfalto; Cisalhamento de interface; Fadiga por cisalhamento; Paving geosynthetic; Asphalt overlays; Interface bond; Shear fatigue; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA; ENGENHARIAS::ENGENHARIA CIVIL